Evolution of tonal organization in music mirrors symbolic representation of perceptual reality. Part-1: Prehistoric - Nikolsky, Aleksey (Frontiers in Psychology, 2015)
This paper reveals the way in which musical pitch works as a peculiar form of cognition that reflects upon the organization of the surrounding world as perceived by majority of music users within a socio-cultural formation. The evidence from music theory, ethnography, archeology, organology, anthropology, psychoacoustics, and evolutionary biology is plotted against experimental evidence. Much of the methodology for this investigation comes from studies conducted within the territory of the former USSR. To date, this methodology has remained solely confined to Russian speaking scholars. A brief overview of pitch-set theory demonstrates the need to distinguish between vertical and horizontal harmony, laying out the framework for virtual music space that operates according to the perceptual laws of tonal gravity. Brought to life by bifurcation of music and speech, tonal gravity passed through eleven discrete stages of development until the onset of tonality in the 17th century. Each stage presents its own method of integration of separate musical tones into an auditory-cognitive unity. The theory of “melodic intonation” is set forth as a counterpart to harmonic theory of chords. Notions of tonality, modality, key, diatonicity, chromaticism, alteration, and modulation are defined in terms of their perception, and categorized according to the way in which they have developed historically. Tonal organization in music, and perspective organization in fine arts are explained as products of the same underlying mental process. Music seems to act as a unique medium of symbolic representation of reality through the concept of pitch. Tonal organization of pitch reflects the culture of thinking, adopted as a standard within a community of music users. Tonal organization might be a naturally formed system of optimizing individual perception of reality within a social group and its immediate environment, setting conventional standards of intellectual and emotional intelligence.